Rancang Bangun Aplikasi Toko Bunga Berbasis Web Menggunakan Waterfall dan Pieces - Fikar Wahyu Tyas Tono; Agung Triayudi; Ratih Titi Komala Sari (KITA Institute, 2022)
Along with the current development of digitalization technology, almost all aspects have adapted to these changes, including the Indonesian people, who are mostly traders, also take part in this development. The website is one of the digitalization models that is often used in promoting products, both goods and Services, in this case the author takes one example, namely the sale of a flower shop